Heavy metal music prefference, delinquent friends, social control, and delinquency - Singer, Simon I. (Journal of research in crime and delinquency, 1993)
The authors examined the relationship between a preference for heavy metal music among a large sample of suburban high school youth (N = 715) and delinquency, controlling for parental and school-related variables, as well as delinquent associations. They found support for the hypothesis that heavy metal has an effect on delinquency when parental control is low. However, they found no support for the hypothesized interaction between a preference for heavy metal and delinquent peers. Contrary to expectations, those students with better school marks and a preference for heavy metal music had higher amounts of self-reported delinquency. [ABSTRACT FROM AUTHOR]